The Purpose of Keeping Records towards the Development of Government Hospitals. A Case Study of Kabale Referral Hospital in Kabale District - Pamela, Naturinda (Kabale University, 2019)
The study was entitled “the importance of keeping records towards the development of government hospitals: a case study of Kabale Referral Hospital”. The objectives of the study were; to identify various types of records kept in Government Hospitals, to investigate the purpose of keeping records in Government Hospitals, to establish the challenges affecting records keeping in Government Hospitals and to find out the strategies to enhance record keeping in government hospitals. The research design employed was both qualitative and quantitative and the researcher used research instruments such as Questionnaire, Observation and Interview methods, the target population was fifty (50) that is administrators, staff and clients of the Hospital. The findings of the study revealed that there were very many challenges affecting records management such as lack of enough funds inadequate files, misfiling, lack of enough computers, lack of enough reading space and Quick deterioration of records. The study also discovered that in order to overcome the above challenges, there should be use of modern technology, updating records, use of proper storage trained staff. The study recommends that Government should facilitate the Hospital, its requirements such as computers, use of modern technology, updating records, use of proper storage and trained staff to improve the services of the Hospital. The study recommends that there should be qualified records staff members, staff development and training of the records staff, electronic filing should be embraced, trained staff should be employed, large store should be provided in improve services of the Hospital.